HUBUNGAN KEKURANGAN ENERGI KRONIS (KEK) PADA REMAJA PUTRI DENGAN SIKLUS MESTRUASI DI SMAN 2 TAMBANG - Antika Pratiwi; Yesi Septina Wati; Meirita Herawati; Rifa Yanti (Ensiklopedia Research and Community Service Review, 2026)
Chronic Energy Deficiency (CED) is a nutritional problem that is still commonly found among adolescent girls and can affect reproductive health, one of which is menstrual cycle disorders. An irregular menstrual cycle in adolescent girls may indicate hormonal imbalance influenced by nutritional status. This study aimed to determine the relationship between Chronic Energy Deficiency (CED) in adolescent girls and menstrual cycle patterns at SMAN 2 Tambang. This study employed an analytical observational design with a cross-sectional approach. The population consisted of all tenth-grade female students at SMAN 2 Tambang, totaling 40 respondents, with the sampling technique using total sampling. Nutritional status data were obtained through Mid-Upper Arm Circumference (MUAC) measurements, while menstrual cycle data were collected using a questionnaire. Data analysis was conducted using univariate and bivariate analysis with Fisher’s Exact Test. The results showed that out of 40 adolescent girls, 13 respondents (32.5%) experienced Chronic Energy Deficiency (CED), while 27 respondents (67.5%) had normal nutritional status. A total of 25 respondents (62.5%) had a normal menstrual cycle, while 15 respondents (37.5%) experienced an irregular menstrual cycle. Bivariate analysis indicated a significant relationship between Chronic Energy Deficiency (CED) and menstrual cycle patterns among adolescent girls at SMAN 2 Tambang, with a p-value of 0.001. In conclusion, there is a significant relationship between Chronic Energy Deficiency (CED) and menstrual cycle patterns in adolescent girls. Therefore, efforts to improve nutritional status and provide balanced nutrition education for adolescent girls are needed to maintain reproductive health and regular menstrual cycles.Keyword : Chronic Energy Deficiency, Menstrual Cycle, Adolescent Girls